Association of renin and aldosterone with glucose metabolism in a Western European population: the KORA F4/FF4 study. Issue 1 (27th January 2022) - Then, Cornelia; Ritzel, Katrin; Herder, Christian; Then, Holger; Sujana, Chaterina; Heier, Margit; Meisinger, Christa; Peters, Annette; Koenig, Wolfgang; Rathmann, Wolfgang; Roden, Michael; Maalmi, Haifa; et al.
Abstract : Introduction: Primary aldosteronism is associated with impaired glucose tolerance. Whether plasma aldosterone and/or renin concentrations are associated with type 2 diabetes and continuous measures of glucose metabolism in the general population is still under debate. Research design and methods: The analyses included 2931 participants of the KORA F4 study at baseline and 2010 participants of the KORA FF4 study after a median follow-up of 6.5 years. The associations of active plasma renin and aldosterone concentrations with type 2 diabetes and continuous measures of glucose metabolism were assessed using logistic and linear regression models. Results were adjusted for sex, age, body mass index (BMI), estimated glomerular filtration rate, potassium, use of ACE inhibitors, angiotensin receptor blockers, beta blockers, diuretics and calcium channel blockers. Results: Cross-sectionally, renin was associated with type 2 diabetes (OR per SD: 1.25, 95% CI 1.10 to 1.43, p<0.001), fasting glucose, 2-hour glucose, insulin, proinsulin, HOMA-B (homeostasis model assessment of beta cell function) and HOMA-IR (homeostasis model assessment of insulin resistance) (all p values <0.001). Aldosterone was not associated with type 2 diabetes (OR: 1.04, 95% CI 0.91 to 1.19; p=0.547) but with insulin, proinsulin and HOMA-IR (all p values <0.001). The aldosterone–renin ratio was inversely associated with type 2 diabetes and several measures of glucose metabolism. Longitudinally, neither renin (OR: 1.12, 95% CI 0.92 to 1.36) nor aldosterone (OR: 0.91, 95% CI 0.74 to 1.11) were associated with incident type 2 diabetes. Renin was inversely associated with changes of insulin concentrations. Conclusions: In the KORA F4/FF4 study, renin and aldosterone were not associated with incident type 2 diabetes and largely unrelated to changes of measures of glucose metabolism. Cross-sectionally, aldosterone was associated with surrogate parameters of insulin resistance. However, these associations were not independent of renin.